The Lin28/Let-7 System in Early Human Embryonic Tissue and Ectopic Pregnancy - Lozoya, Teresa; Domínguez, Francisco; Romero-Ruiz, Antonio; Steffani, Liliana; Martínez, Sebastián; Monterde, Mercedes; Ferri, Blanca; Núñez, Maria Jose; AinhoaRomero-Espinós; Zamora, Omar; Gurrea, Marta; Sangiao-Alvarellos, Susana; et al. (PLOS ONE, 2014)
Our objective was to determine the expression of the elements of the Lin28/Let-7 system, and related microRNAs (miRNAs), in early stages of human placentation and ectopic pregnancy, as a means to assess the potential role of this molecular hub in the pathogenesis of ectopic gestation. Seventeen patients suffering from tubal ectopic pregnancy (cases) and forty-three women with normal on-going gestation that desired voluntary termination of pregnancy (VTOP; controls) were recruited for the study. Embryonic tissues were subjected to RNA extraction and quantitative PCR analyses for LIN28B, Let-7a, miR-132, miR-145 and mir-323-3p were performed. Our results demonstrate that the expression of LIN28B mRNA was barely detectable in embryonic tissue from early stages of gestation and sharply increased thereafter to plateau between gestational weeks 7–9. In contrast, expression levels of Let-7, mir-132 and mir-145 were high in embryonic tissue from early gestations (≤6-weeks) and abruptly declined thereafter, especially for Let-7. Opposite trends were detected for mir-323-3p. Embryonic expression of LIN28B mRNA was higher in early stages (≤6-weeks) of ectopic pregnancy than in normal gestation. In contrast, Let-7a expression was significantly lower in early ectopic pregnancies, while miR-132 and miR-145 levels were not altered. Expression of mir-323-3p was also suppressed in ectopic embryonic tissue. We are the first to document reciprocal changes in the expression profiles of the gene encoding the RNA-binding protein, LIN28B, and the related miRNAs, Let-7a, mir-132 and mir-145, in early stages of human placentation. This finding suggests the potential involvement of LIN28B/Let-7 (de)regulated pathways in the pathophysiology of ectopic pregnancy in humans.